VITAMINS’ DEFICIENCY IN CHILDREN DURING AUTUMN - O.A. Gromova; V.G. Rebrov (Вопросы современной педиатрии, 2009)
Suboptimal provision with vitamins is widely spread among children. Its significance, to a considerable degree, is determined by season, and the most active forming of vitamins’ insufficiency occurs in the beginning of autumn. The necessity of correction of these states is assigned with the fact that the most of the vitamins are water-soluble, and organism can’t accumulate it. The administration of vitamin complexes allows achieving proper compensation of present vitamins’ insufficiency, and to prevent its development in future. Key words: children, vitamins, insufficiency, season. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(5):111-114)